2016
DOI: 10.4038/tare.v17i2.5311
|View full text |Cite
|
Sign up to set email alerts
|

Callus formation and organogenesis of tomato (Lycopersicon escu-lentum mill variety Thilina)

Abstract: This study was conducted to investigate the effects of explant source and hormone concentrations on the callogenesis, calli growth, plantlet regeneration and rooting of a local tomato variety (Lycopersicon esculentum mill. variety 'Thilina'). Different combinations of Benzyl Adenine (BAP) and 2, 4-Dichlorophenoxyacetic acid (2, 4-D) were used with hypocotyl, leaf and root explants in a completely randomized design with five replicates to evaluate the success in plantlet regeneration. Regenerated healthy shoots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Moreover, Hnur and Krishnareddy (2016) clearly indicated the role of kinetin with BAP into produce good embryogenic calli from hypocotyls explants in tomato and developed them to whole plantlets. Furthermore, many researchers have reported that kinetin and BA as important cytokinins with high shoot regeneration ability from hypocotyl explants when used in combination with some auxins such as NAA in the culture medium (Manawadu et al, 2014). Kauser et al (2016) as well showed that the combination of 1.5mgl -1 BAP, 0.5mgl -1 zeatin and 0.2mgl -1 IAA was considered as the best medium for high plant regeneration rates from hypocotyl, cotyledon and leaf explants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Hnur and Krishnareddy (2016) clearly indicated the role of kinetin with BAP into produce good embryogenic calli from hypocotyls explants in tomato and developed them to whole plantlets. Furthermore, many researchers have reported that kinetin and BA as important cytokinins with high shoot regeneration ability from hypocotyl explants when used in combination with some auxins such as NAA in the culture medium (Manawadu et al, 2014). Kauser et al (2016) as well showed that the combination of 1.5mgl -1 BAP, 0.5mgl -1 zeatin and 0.2mgl -1 IAA was considered as the best medium for high plant regeneration rates from hypocotyl, cotyledon and leaf explants.…”
Section: Discussionmentioning
confidence: 99%
“…The reason of lower organogenesis percentage and shoots number from leaf explants comparing with cotyledon and hypocotyl explants in this study may be due to the type of explants as well as the type of plant growth regulators and concentration (Majoul et al, 2007). However, other research found that the better explants for direct regeneration was the leaf bud when cultured on MS medium supplemented with 0.5 mgl -1 kinetin +2.0 mgl -1 BAP + 0.1 mgl -1 NAA (Manawadu et al, 2014). Figure 1: Direct organogenesis in tomato cv.…”
Section: Gharbia Danial -Diaa Ibrahimmentioning
confidence: 99%
See 1 more Smart Citation
“…26 TDZ encourages purine-type cytokinin synthesis and hence promote callus growth and regeneration in the hypocotyl tissues of Pelargonium hortorum by controlling the auxin transport and changing or stimulating the levels of abscisic acid, ethylene, and prolines. 123 An increase in the ribonucleoside level may cause the biological activity of TDZ. 92 It also increases the purine supply for cellular development and accumulates the metabolites of purine and also converts adenine to adenosine.…”
Section: Callogenesis By Thidiazuron Inducing Other Plant Growth Regu...mentioning
confidence: 99%
“…Solanum lycopersicum Mill. is the member of Solanaceae family and one of the most important vegatable crop grown at the different part of the world (Manawadu et al, 2014).It contains a lof of nutrients and antioxidants (lycopene, phenol, flavonoid, vitamin C) which are quite important as food and for the the human health (Periago et al, 2009). However, heavy metal impacts on food production and human health have become a global concern all over the world.…”
Section: Introductionmentioning
confidence: 99%